The Effect of Problem Based Instruction Model Using Telegram Quiz Bot on Students’ Learning Motivation - Nasution, Eline Yanty Putri; Putri Yulia (Universitas Wiralodra, 2023)
This research is a quantitative research with the quasi experimental research type. The population in this study were all Semester V students of the Mathematics Education Department (TMTK) IAIN Kerinci and the samples were 30 students of VA class through purposive sampling technique. Data collection techniques used in this study were observation sheets and questionnaires. The purpose of this study was to find out how the application of the Problem Based Instruction (PBI) learning model using Telegram Quiz Bot, to find out how the students’ mathematics learning motivation, and to find out how the relationship between the PBI learning model using the Telegram Quiz Bot and the students’ mathematics learning motivation. The findings show that the use of the PBI learning model using Telegram Quiz Bot in the VA class obtained an average value of 3.1 which is included in the